Challenges and Opportunities for North Lombok Robusta Coffee - Zainuri, Zainuri; Sjah, Taslim; Budastra, I Ketut; Dipokusumo, Bambang; Iqlimawati, Iqlimawati (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Robusta coffee is an important agricultural commodity in North Lombok Regency, Indonesia, contributing to rural livelihoods and regional economic development. However, the performance of the Robusta coffee agribusiness remains constrained by various external challenges while simultaneously presenting emerging opportunities. This study aims to identify and analyze the key challenges and opportunities affecting the development of Robusta coffee in North Lombok, and proposes strategies for expanding market for North Lombok Robusta coffee. The results show that the main challenges identified include fluctuating coffee prices, the low bargaining position of farmers and processors, inconsistent coffee bean quality, and limited access to subsidized fertilizers. Conversely, significant opportunities arise from increasing domestic and global demand for coffee, availability of government support programs, the potential for value-added coffee processing, and improved access to market and technical information. The findings indicate that opportunity-driven strategies, particularly those related to value addition, quality improvement, sustainable input management, and information utilization, can mitigate existing challenges and enhance the competitiveness and sustainability of the Robusta coffee agribusiness in North Lombok. The study provides policy-relevant insights for stakeholders involved in regional coffee development, by outlining concrete intervention areas, such as productivity enhancement, quality improvement, institutional strengthening, and market access expansion, to support value chain upgrading and sustainable Robusta coffee development in North Lombok. The novelty of this study lies in its integration of regency-level analysis of Robusta coffee in North Lombok and reconceptualizes Robusta from a low-value commodity into high-value one through expanding markets with differentiated emerging specialty and sustainable products.